Does the definition of chronic active T cell–mediated rejection need revisiting?. Issue 5 (22nd December 2020) - Naesens, Maarten; Haas, Mark; Loupy, Alexandre; Roufosse, Candice; Mengel, Michael
Abstract : Members of the Banff Consortium for Allograft Pathology reflect on recent findings from the comprehensive analysis of the DeKAF study cohorts on applying the newly introduced Banff criteria for chronic‐active T cell–mediated rejection, indicating that further refinement of this new Banff diagnostic category is warranted. See Helgeson et al.'s article on page 1866 .